Evaluation of soil moisture and evapotranspiration variation using water balance methods in Indian Mustard (Brassica juncea) - KUMAR, ROHITASHW; RICHA, RISHI; KUMAR, MUKESH (Journal of Soil and Water Conservation, 2023)
The field experimental was carried out to determine soil moisture regime and evaporation in Indian Mustard (Brassica juncea) in sub humid area of Himachal Pradesh. A field crop investigation was conducted to understand the effect of moisture and crop evapotranspiration (ETc) on agro-climatic variables i.e., canopy temperature (Tc), and soil moisture content (SMC) in the root zone. Lysimeters set up was used with different crop spacing patterns in the study. The results of the experimental study soil moisture content in the root zone were directly related to the crop density. The crop evapotranspiration calculated by P-T, H-S, Fc- Pen and P-M overestimate but P-M model shows slightly differences than observed value. F B-C and F E-pan underestimate significantly. The COD, SEE and ARE values varies; 0.44 to 0.96; 7.46 to 38.98 and -27.4 to 21.23, respectively using different models. P-M model gives close agreement with COD, SEE and ARE values; 0.96, 7.46 and 14.21, respectively. The crop spacing did not influence the total seasonal ETc, but stage-wise ETc exhibited some variation. The study can help better understand the agro-climatic processes and their dependence on crop spacing.